Developing simulation model for solid state power controller shutdown techniques - Amar Mahesh Kumar (2015)
This report represents the development of the simulation model of Solid State Power Controllers (SSPC) and demonstrating the shutdown mechanism by MATLAB-SIMULINK Software. The project started with understanding the applications and purpose of using SSPC which is being widely getting used in the aerospace power systems in the commercial as well as defence aircrafts worldwide. The market research has been done to understand the applications, features of the market available SSPC's and captured the details in subsequent sections. A lot of white papers and journal papers have been published in this area on realistic simulation of the SSPC and its shutdown techniques. A through literature survey has been done on this area to understand the trend and challenges of the practical fields and simulation possibility of the fault scenarios. A couple of simulation environments were studied and the suitable one is chosen to simulate the SSPC model after analysis the pros and cons in each of them. The model has been developed using datasheets of the market available SSPC's too deeply understand the behaviour of the part. A few fault cases have been tested and possible ways and settings to mitigate the faults have been suggested. Finally the conclusion and future scope has been identified and captured along with the simulation results which sets the right direction for future implementation and study on this area.